2004
DOI: 10.1111/j.1538-7836.2004.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations in EGF‐like domains of human factor IX dramatically impair intracellular processing and secretion

Abstract: We investigated the mechanisms responsible for severe factor IX (FIX) deficiency in two cross-reacting material (CRM)-negative hemophilia B patients with a mutation in the first and second epidermal growth factor (EGF) domains of FIX (C71Y and C109Y, respectively). We have determined the kinetics of mutant FIX biosynthesis and secretion in comparison with wild-type FIX (FIXwt). In transfected cells, FIXwt was retrieved as two intracellular molecular forms, rapidly secreted into the culture medium. One appeared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
(34 reference statements)
2
23
0
Order By: Relevance
“…Non-synonymous mutations (altering protein structure) in the second EGF-like domain (where Val107Val mutation is located) were shown to cause impaired intracellular processing and secretion 26. Current knowledge about the effects of synonymous mutations on protein function suggests that they can also alter protein structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-synonymous mutations (altering protein structure) in the second EGF-like domain (where Val107Val mutation is located) were shown to cause impaired intracellular processing and secretion 26. Current knowledge about the effects of synonymous mutations on protein function suggests that they can also alter protein structure.…”
Section: Resultsmentioning
confidence: 99%
“…These are associated with subtle changes in its structure caused by altered translation dynamics (figure 3). Note that non-synonymous mutations in the second EGF-like domain were previously shown to cause FIX impaired intracellular processing and secretion 26. We have previously presented an extensive review of the multiple mechanisms by which synonymous mutations affect protein structure and function and the methods that may be used to study these 4.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of the Cys141 (Cys95)-Cys155 (Cys109) disulfide bond could lead to a FIX activity less than 1% [6]. A previous study showed that mutant FIX carrying Cys155Tyr (Cys109Tyr) was not secreted from the cells and did not accumulate intracellularly [18].…”
Section: Discussionmentioning
confidence: 99%
“…Other changes, e.g. in the epidermal growth factor-like domain, can negatively influence secretion of this glycoprotein [122,123]. On the other hand, targeted changes and modifications to this clotting factor can significantly improve its activity and prolong its lifetime in the bloodstream.…”
Section: Clotting Factor IXmentioning
confidence: 97%